Expert consensus on the off-label use in China of drugs for rare hematologic diseases (2024 edition) - Zhao, Boxin; Zhou, Xuan; Zheng, Ping; Zhang, Bo; Feng, Xiaoqin; Chen, Jie; Cai, Lisheng; Chen, Yilu; He, Liya; Su, Jianfen; Cheng, Shuqin; Zeng, Yingtong; et al. (Frontiers in Pharmacology, 2024)
Drug package inserts are a crucial foundation for clinical medication practices and serve as the legal basis for guiding rational drug use and ensuring patient safety and efficacy. As rare disease treatments evolve, current package inserts often need to meet the clinical requirements for treating such conditions, frequently resulting in off-label drug use. This consensus is derived from discussions between Guangdong Pharmaceutical Association Hematologic Rare Diseases Group experts. The consensus aims to provide a framework and reference for the clinical application of off-label drug use in treating rare hematologic diseases.